Evaluation of Existing Research Concerning Sustainability in the Value Chain of Ornamental Plants - Dominguez, Gabriela Bermejo; Mibus-Schoppe, Heiko; Sparke, Kai (European Journal of Sustainable Development, 2017)
In recent years the concept of "Sustainable Development" has become increasingly relevant in society as well as for the economy. Like in other consumer spending areas, sustainability is getting an increasing role in the ornamental plant production, marketing and consumption. Research in the production area has been focused on achieving a better quality and longevity of ornamentals at point of sale and also on environmental aspects as part of sustainability. The maintenance of the quality and longevity of the plants until the point of sale have been the objectives of post-harvest handling and distribution. At consumer level studies show that the well-being and the indoor quality improvement are the main reasons for having ornamentals. However the concept of sustainability has not been investigated throughout the entire ornamental plant value chain. Economic and interdisciplinary factors play a role in this lack of studies. By analysing the existing literature, the paper evaluates in which areas of the value chain the concept of sustainability have not been considered and identifies potential future steps to reach a more sustainable complete lifecycle of ornamentals. Keywords: Sustainability, ornamental plants, horticulture, value chain